2019
DOI: 10.47176/mjiri.33.60
|View full text |Cite
|
Sign up to set email alerts
|

Proprioception in stress urinary incontinence: A narrative review

Abstract: Background: Urinary incontinence (UI) is more common than any other chronic disease. Stress urinary incontinence (SUI), among the various forms of urinary incontinence, is the most prevalent (50%) type of this condition. Female urinary continence is maintained through an integrated function of pelvic floor muscles (PFMs), fascial structures, nerves, supporting ligaments, and the vagina. In women with SUI, the postural activity of the PFMs is delayed and the balance ability is decreased. Many women, by learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
7
0
5
Order By: Relevance
“…Many studies have demonstrated the power and specificity of verbal instructions [18][19][20][21][22]. The single use of verbal instructions has been shown to have an impact on the distribution of activity in complementary muscles and postural muscles during different activities without any changes in the exercise performance [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated the power and specificity of verbal instructions [18][19][20][21][22]. The single use of verbal instructions has been shown to have an impact on the distribution of activity in complementary muscles and postural muscles during different activities without any changes in the exercise performance [19].…”
Section: Introductionmentioning
confidence: 99%
“…The single use of verbal instructions has been shown to have an impact on the distribution of activity in complementary muscles and postural muscles during different activities without any changes in the exercise performance [19]. More specifically, several authors have studied the effect of verbal instructions on pelvic floor exercises performance, these studies were based in the influence of proprioceptive input in muscle activity timing, coordination, balance and posture [18,21,22]. In the study of Stafford et al [21], the activation pattern of the PFM in a sample of men was influenced by verbal instructions.…”
Section: Introductionmentioning
confidence: 99%
“…It had been proved that acupotomy was beneficial to reduce pain and improve joint function for KOA patients [ 45 ], which resulted in a better proprioception before intervention. On the other hand, the proprioception mainly includes the sense of position and movement and the sense of effort, force, and heaviness [ 46 ], and tendons and muscle spindles are the two major mechanoreceptors [ 47 ]. As was reported, muscle weakness or atrophy appeared in patients with OA as one of the earliest symptoms [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alongside this, weakened pelvic floor Open Access *Correspondence: M_kamali1984@yahoo.com muscles are linked with urinary incontinence, the most frequently reported symptom among pelvic floor disorders [2]. Stress urinary incontinence (SUI) is the most common type of urinary incontinence, with a prevalence of 50% [3]; its prevalence among Iranian women aged 40 to 50 is approximately 38.4% [4]. SUI occurs during times of elevated intraabdominal pressure (e.g., sneezing, coughing, and exercise) [5].…”
Section: Introductionmentioning
confidence: 99%